The Relationship between Inclusive Leadership and corporate entrepreneurship: Analytical Research in the Ministry of Higher Education and Scientific Research - ASSAD, MUSTAFA ABDULABBAS; MOHAMMED, DR. NISREEN JASIM (The journal of contemporary issues in business and government, 2021)
The main objective of the research is to verify the relationship and influence between the inclusive leadership and the corporate entrepreneurship in the Iraqi Ministry of Higher Education and Scientific Research, and to identify the reality of the behaviors and processes of the inclusive leadership prevailing among the administrative leaderships in the ministry in order to develop appropriate mechanisms and procedures that work to create a culture of inclusive leadership style Which enhances belonging and exclusivity among all employees and encourages creativity and innovation and directs them towards achieving corporate entrepreneurship. Data were collected from an intentional sample of the administrative leaders working in the researched ministry and consisted of (150) respondents, and for the purpose of data analysis, and the statistical programs (SPSS, AMOS) were added by adopting statistical methods. The results showed the correctness of the correlation and influence relationships at the level of major variables and sub-dimensions, indicating the essential role of inclusive leadership to achieve the corporate entrepreneurship in the Ministry of Higher Education and Scientific Research.